Camptothecin Inhibits Neddylation to Activate the Protective Autophagy Through NF-κB/AMPK/mTOR/ULK1 Axis in Human Esophageal Cancer Cells - Heng, Yongqing; Liang, Yupei; Zhang, Junqian; Li, Lihui; Zhang, Wenjuan; Jiang, Yanyu; Wang, Shiwen; Jia, Lijun (Frontiers in Oncology, 2021)
The neddylation pathway is overactivated in esophageal cancer. Our previous studies indicated that inactivation of neddylation by the NAE inhibitor induced apoptosis and autophagy in cancer cells. Camptothecin(CPT), a well-known anticancer agent, could induce apoptosis and autophagy in cancer cells. However, whether CPT could affect the neddylation pathway and the molecular mechanisms of CPT-induced autophagy in esophageal cancer remain elusive. We found that CPT induced apoptosis and autophagy in esophageal cancer. Mechanistically, CPT inhibited the activity of neddylation and induced the accumulation of its substrate IκBα to block NF-κB activation. Furthermore, CPT induced the generation of ROS to modulate the AMPK/mTOR/ULK1 axis to finally promote protective autophagy. In our study, we elucidate a novel mechanism of NF-κB/AMPK/mTOR/ULK1 pathway in CPT-induced protective autophagy in esophageal cancer cells, which provides a sound rationale for combinational anti-ESCC therapy with CPT and inhibition AMPK/ULK1 pathway.